Two pumps or one pump? A comparison of human liver normothermic machine perfusion devices for transplantation. Issue 5 (28th December 2021) - Liu, Qiang; Del Prete, Luca; Hassan, Ahmed; Pezzati, Daniele; Bilancini, Mary; D'Amico, Giuseppe; Diago Uso, Teresa; Hashimoto, Koji; Aucejo, Federico; Fujiki, Masato; Sasaki, Kazunari; Kwon, Choon Hyuck David; et al.
Abstract: Background: Normothermic machine perfusion provides continuous perfusion to ex situ hepatic grafts through the portal vein and the hepatic artery. Because the portal vein has high flow with low pressure and the hepatic artery has low flow with high pressure, different types of perfusion machines have been employed to match the two vessels' infusion hemodynamics. Methods: We compared transplanted human livers perfused through a 2‐pump ( n  = 9) versus a 1‐pump perfusion system ( n  = 6) where a C‐clamp is used as a tubing constrictor to regulate hemodynamics. Results: There was no significant difference between groups in portal vein or hepatic artery flow rate. The 1‐pump group had more hemoglobin in the perfusate. However, there was no significant difference in plasma hemoglobin between the 2‐pump and 1‐pump groups at each time point or in the change in levels, proving no hemolysis occurred due to C‐clamp tube constriction. After transplantation, the 2‐pump group had two cases of early allograft dysfunction (EAD), whereas the 1‐pump group had no EAD. There was no graft failure or patient death in either group during follow‐up ranging from 20–52 months. Conclusions: Our data show that the 1‐pump design provided the same hemodynamic output as the 2‐pump design, with no additional hemolytic risk, but with the benefits of lower costs, easier transport and faster and simpler setting. Abstract : Normothermic machine perfusion preservation on liver grafts had different types of perfusion machines to meet the hemodynamic requirement at portal vein and hepatic artery. This study indicated that the 1‐pump system using a C‐clamp as tube constrictor on portal infusion can provide similar hemodynamics to a 2‐pump system and with no additional hemolytic risk.